A note on a ginger (Zingiber officinale Rosc.) type collected from Western Ghats, South India - ZACHARIAH, B SASIKUMAR, K JOHNSON GEORGE, T JOHN (Journal of Spices and Aromatic Crops, 1995)
Even though South East Asia is considered to be the centre of origin of ginger (Zingiber officinale Rosc.) (Bailey 1949), there are very few reports of ginger occurring in the wild’ state. Fisher (1921) recorded that ginger was seen apparently in wild conditions in the Anamalais at about 2300 ft elevation. Muralidharan & Velayudhan (1983) also indicated the possibility of ginger growing as a component of natural vegetation in pockets of Western Ghats at higher altitudes.